Saving behaviour and global imbalances: the role of emerging market economies - Gianluigi Ferrucci; Cesar Miralles (European Central Bank (ECB), 2007)
In recent years there has been considerable variation in savings patterns across countries and regions, with implications for the configuration of global current account balances, asset valuations and real interest rates. This paper looks at the empirical drivers behind these trends. It uses a reduced-form model that relates private savings to a set of economic fundamentals, while controlling for structural and institutional differences across countries. Addressing a typical shortcoming of the previous literature, estimates are obtained from a dynamic model, which accounts for cross-sectional heterogeneity. The results suggest that saving rates in emerging economies are higher than cross-country estimates based on fundamentals, particularly in Asia. Demographic factors and financial catching-up have been key drivers of the observed changes in savings in these economies. Looking ahead, the prospective population aging is likely to lead to a considerable fall in saving rates in many economies - albeit the process will take decades to unfold. Further progress in financial deepening in developing economies may be conducive to a redistribution of international saving flows and may potentially support a smoother adjustment of global imbalances.
Keywords: E20; E60; 330; emerging economies; global imbalances; panel error correction model; pooled mean group estimation; Private savings; Sparquote; Sparen; Leistungsbilanz; Realzins; Institutionelle Infrastruktur; Schwellenländer